1997
DOI: 10.1021/bi963120l
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of P-Glycoprotein with Defined Phospholipid Bilayers:  A Differential Scanning Calorimetric Study

Abstract: One of the major causes of multidrug resistance in human cancers is expression of the P-glycoprotein multidrug transporter, which acts as a drug efflux pump. P-Glycoprotein is a member of the ABC superfamily of membrane proteins, and is composed of 12 hydrophobic membrane-spanning segments and 2 cytoplasmic nucleotide binding domains. Membrane lipids are known to play an important role in the function of P-glycoprotein. In the present study, purified P-glycoprotein of high specific ATPase activity was reconsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 42 publications
2
49
1
Order By: Relevance
“…In the case of Pgp, it appears that a rate-limiting step is, in fact, enhanced when the host lipid is in the gel phase. Along the same lines, we recently reported [35] that Pgp was reconstituted into Myr 2GroPCho with higher efficiency and specific ATPase activity at temperatures below t m , suggesting that the protein may have a preference for gel-phase lipid. Clearly, the nature of the chemical barrier for catalysis by Pgp is affected by the lipid-phase state quite differently than for other membrane-bound enzymes.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In the case of Pgp, it appears that a rate-limiting step is, in fact, enhanced when the host lipid is in the gel phase. Along the same lines, we recently reported [35] that Pgp was reconstituted into Myr 2GroPCho with higher efficiency and specific ATPase activity at temperatures below t m , suggesting that the protein may have a preference for gel-phase lipid. Clearly, the nature of the chemical barrier for catalysis by Pgp is affected by the lipid-phase state quite differently than for other membrane-bound enzymes.…”
Section: Discussionmentioning
confidence: 53%
“…SDS/PAGE was carried out as described previously [22]. Differential scanning calorimetry (DSC) measurements were used to determine the gel/ liquid-crystalline phase transition temperature, t m , of liposomes of PamMyrGroPCho and Myr 2 GroPCho alone, and proteoliposomes of PamMyrGroPCho and Myr 2 GroPCho containing 13:1 (by mass) and 10:1 (by mass) Pgp, respectively, as described previously [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detergents and additional adjuvants from the purification and reconstitution procedures can affect the behavior of the transporter, as we have shown for CHAPS. The most frequently used detergents for the purification of P-gp beside CHAPS (26,28,29,32,39,42) are n-octyl b-D-glucopyranoside (octyl glucoside) (27,30,(49)(50)(51)(52)(53) and n-dodecyl or n-decyl b-Dmaltoside (14,22,25,33,51,(54)(55)(56). Octyl glucoside had activating as well as inhibiting effects on the ATPase activity of CHAPS-solubilized P-gp, depending on the glucoside concentration (39).…”
Section: Discussionmentioning
confidence: 99%
“…The linearity of the plots indicated that single overall rate-limiting steps were being observed. In contrast, some plasma membrane preparations and Pgp reconstituted in synthetic lipid mixtures did not produce linear Arrhenius relationships due to lipid phase transitions and other effects (43)(44)(45). Arrhenius relationships were measured for the drugs listed above as a function of concentration such that all phases of drug-dependent ATPase activities were investigated.…”
Section: Tight Coupling Of Atp-binding and Drug Transport Sites-mentioning
confidence: 99%